Students’ Perceptions of TalentLMS as a Supporting Tool for Learning English Outside the Classroom : - Wahyu Septian Winduaji; Juang Kurniawan (Universitas PGRI Yogyakarta, 2026)
This study aims to explore students’ perceptions of using TalentLMS as a supporting tool for learning English outside the classroom. This research employed a qualitative descriptive design to obtain a deeper understanding of students’ experiences and perspectives regarding the use of TalentLMS in English learning activities. The participants of this study were five students of the English Education Study Program who had experience using TalentLMS for learning English outside classroom instruction. The data were collected through semi-structured interviews and analyzed using thematic analysis. The findings revealed that students generally had positive perceptions toward the use of TalentLMS. Students perceived the platform as easy to use because of its simple interface and accessible features. In addition, TalentLMS was considered useful in helping students access learning materials, complete exercises, and support independent learning outside the classroom. The platform also provided flexibility because students could learn anytime and anywhere according to their own learning pace. Furthermore, TalentLMS encouraged learner autonomy by allowing students to review materials and practice English independently. However, several challenges were also identified, including internet connection problems and limited interaction during online learning activities. In conclusion, TalentLMS can support English learning outside the classroom by providing flexible and accessible learning opportunities for students. Keywords: TalentLMS; Learning Outside the Classroom; Students’ Perceptions; LMS; English Language Learning